2019
DOI: 10.1186/s12877-019-1057-7
|View full text |Cite
|
Sign up to set email alerts
|

The associations of multimorbidity with the sum of annual medical and long-term care expenditures in Japan

Abstract: Background The occurrence of multimorbidity (i.e., the coexistence of multiple chronic diseases) increases with age in older adults and is a growing concern worldwide. Multimorbidity has been reported to be a driving factor in the increase of medical expenditures in OECD countries. However, to the best of our knowledge, there is no published research that has examined the associations between multimorbidity and either long-term care (LTC) expenditure or the sum of medical and LTC expenditures worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 27 publications
(32 reference statements)
3
45
0
Order By: Relevance
“…Indeed, the previous studies based on claims data from one city in Japan suggested that there is a trade-off between medical and LTC expenditures; hence, it is important to include both medical and LTC expenditures when the societal financial burden from multiple diseases is evaluated. 22 , 34 At the time of this analysis, however, national medical insurance claims data could not be merged with national LTCI claims data in Japan. If such a procedure is available in the future, further study, including both medical insurance and LTCI claims data, would be warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the previous studies based on claims data from one city in Japan suggested that there is a trade-off between medical and LTC expenditures; hence, it is important to include both medical and LTC expenditures when the societal financial burden from multiple diseases is evaluated. 22 , 34 At the time of this analysis, however, national medical insurance claims data could not be merged with national LTCI claims data in Japan. If such a procedure is available in the future, further study, including both medical insurance and LTCI claims data, would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Second, morbidity status is not adjusted due to a lack of medical information in the LTCI claims data, even though morbidity status is known to be an important factor in LTC demand. 34 Third, only those who have LTC certifications are included in our study, even though the large variation in LTC certification among regions is an issue. 40 Future study is needed to systematically investigate whether access to LTCI services is equitable.…”
Section: Discussionmentioning
confidence: 99%
“…A person with numerous long-term health conditions has an increased risk of depression, hospitalizations, polypharmacy, loss of physical functioning, and even premature death [5,6]. In addition, multimorbidity places a substantial economic burden on the healthcare system [7][8][9][10], especially in the world's most populous country, China [11,12], because patients with multimorbidity often require additional intensive treatment and monitoring by nurses, physicians and other healthcare staff [13,14]. Therefore, the identification of the key determinants of multimorbidity is an important public health aim that should be addressed urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Family physicians are pivotal in providing care in Japan where the population is rapidly ageing and more patients than ever are presenting with numerous chronic conditions. The prevalence of multimorbidity, the co-occurrence of two or more disorders, was 29.9% among adults and 80.2% among elderly aged 75 or older in Japan [24, 25]. The government and professional bodies need to counteract the limited popularity of family medicine.…”
Section: Discussionmentioning
confidence: 99%